2023
DOI: 10.32604/jrm.2022.022192
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Mechanical Properties and Pore Structure of MSW Incineration Bottom Ash Fine Aggregate Concrete after Freeze-Thaw Cycles Based on the Gray Theory

Abstract: The destruction of concrete building materials in severely cold regions of the north is more severely affected by freeze-thaw cycles, and the relationship between the mechanical properties and pore structure of concrete with fine aggregate from municipal solid waste (MSW) incineration bottom ash after freeze-thaw cycles is analyzed under the degree of freeze-thaw hazard variation. In this paper, the gray correlation method is used to calculate the correlation between the relative dynamic elastic modulus, compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Guo Yisong et al [22] , using plant protein as a foaming agent, prepared foam concrete with a compressive strength of 1.52 MPa. Gao Zhihan et al [23] prepared four types of foam concrete with different densities, having compressive strengths of 1-6 MPa. The compressive strengths of the A, B, and C groups of specimens prepared in this study all exceeded 4 MPa, with the maximum reaching 14.679 MPa, exhibiting excellent protective properties.…”
Section: Analysis Of Porosity Test Resultsmentioning
confidence: 99%
“…Guo Yisong et al [22] , using plant protein as a foaming agent, prepared foam concrete with a compressive strength of 1.52 MPa. Gao Zhihan et al [23] prepared four types of foam concrete with different densities, having compressive strengths of 1-6 MPa. The compressive strengths of the A, B, and C groups of specimens prepared in this study all exceeded 4 MPa, with the maximum reaching 14.679 MPa, exhibiting excellent protective properties.…”
Section: Analysis Of Porosity Test Resultsmentioning
confidence: 99%
“…Guo Yisong [26] found that the compressive strength of foamed concrete prepared using plant protein as a foaming agent was 1.52MPa. Gao Zhihan et al [27] found that the compressive strength of four different density foamed concretes prepared using physical foaming methods was 16MPa. The compressive strength of the A, B, and C specimens prepared in this study all exceeded 11MPa, demonstrating excellent support effects.…”
Section: Study On the Performance Of Foamed Concrete Based On Human H...mentioning
confidence: 99%